PEMUPUKAN ORGANIK UNTUK BUDIDAYA KAKAO YANG BERKELANJUTAN - Aljawas Salampessy, Yudi Lani; Suherna, Suherna; Meilani, Yusi (Universitas Sultan Ageng Tirtayasa, 2020)
Cocoa production of farmers in Gunungsari area has started to decline, both in quantity and quality of the product. This condition results in a decrease in farmers' income, often even causing losses due to production costs higher than product sales. This community service activity was carried out to diffuse the organic farming system and cocoa processing technology. The adoption of these innovations by the farmers became a target of the project. The diffusion of organic farming was conducted through oral and audiovisual communication, field demonstrations, and direct farming assistance. The result showed that the lack of information regarding cultivation technologies and agricultural institutions has led cocoa farming less economical. For this reason, agricultural communication should be further improved through the employment of a variety of communication media and delivery methods. Therefore, the knowledge, attitudes, and enterprise skills of cocoa farmers are able to increase continuously.